Pengembangan Lembar Kegiatan Peserta Didik Berbasis Project Based Learning di Sekolah Dasar - Hadijah Hadijah; Badarudin Badarudin; Aswasulasikin Aswasulasikin (Journal of Elementary School (JOES), 2021)
The purpose of this study was to determine the development of Student Activity Sheets (LKPD) based on Project Based Learning (PJBL) to increase the creativity of fifth graders in thematic learning at SD Negeri Sambelia District. The method used in this research is research and development type ADDIE. Based on research on the development of Project Based Learning-based Student Activity Sheets in class V SD, among others, the Student Activity Sheets that have been developed are declared feasible and valid for use in thematic learning. This is based on the category-worthy results from material experts 77% with appropriate categories, 70% design experts with categories, and linguists 76% with decent categories. Project Based Learning-based Student Activity Sheets that have been developed are stated to be practical for use in thematic learning. This is based on the results of a small-scale trial at SD Negeri 1 Bgaik Manis which received a response of 87% from 5 students with the practical category used. Large-scale trials from public elementary schools in the Sambelia sub-district, namely SD Negeri 1 Bagik Manis, SD Negeri 1 Sambelia, and SD Negeri 1 Sambelia received a response of 81% from 30 students with a very practical category to use. Student activity sheets based on Project Based Learning Have started large-scale trials at SD Negeri 1 Bagik Manis, SD Negeri 2 Sambelia, and SD Negeri 1 Sambelia with an effectiveness test using the Gain Score, namely on the pree test that has obtained an average score The average number of students is 75 and the results of the post- test that have been carried out have an average score of 83.3. Based on the calculation of the effectiveness using the Gain score, the acquisition value of 0.3 is obtained so that the Keyword that the Project-Based Learning-based Student Activity Sheet (LKPD) is already effective. Keywords: Learning Method, Project Based Learning, LKPD